Isolation and identification of symbiotic strains in Paris fargesii Franch that promote disease resistance - Yan, Dahao; Wang, Xianju; Xi, Congfang; Zi, Shuhui; Liu, Tao (Frontiers in Agronomy, 2022)
Pairs polyphylla var. yunnanensis is a perennial herb, and its rhizomes are used as medicine to invigorate blood circulation, dissipate blood stasis, relieve swelling and pain, clear heat and detoxify the body. However, due to its slow growth, most of the saponin content is low, while the content of saponins is higher in Paris fargesii Franch of the same genus. The isolation and screening of strains from P. fargesii Franch that promote the accumulation of saponin content in P. polyphylla var. yunnanensis is important to improve the growth rate of artificially cultivated P. polyphylla var. yunnanensis and increase its medicinal activity. Plant symbiotic strains are biologically active microorganisms that can promote the growth and development of host plants through direct probiotic effects and indirect disease resistance mechanisms. Here, we isolated four strains of symbiotes, including two bacteria, Bacillus cereus (LgD2) and Bacillus thuringiensis (LgD10), and two fungi, Aspergillus tamari (TPD11) and Fusarium oxysporum (TPB). All of them promoted the biomass, chlorophyll content and photosynthetic efficiency of P. polyphylla var. yunnanensis seedlings to different degrees and effectively stimulated the accumulation of saponin content in P. polyphylla var. yunnanensis seedlings to improve the expression of saponin synthesis pathway genes. The symbiotes also promoted the enzymatic activities of the enzymes superoxide dismutase (SOD), peroxidase (POD), polyphenol oxidase (PPO) and phenylalanine aminolase (PAL), improved the physiological indicators of tobacco plants (plant height, crown width, leaf length and leaf width), reduced the incidence of tobacco black shank, and improved the growth and resistance-related genes of tobacco. In conclusion, the four symbiotic strains TPD11, TPB, LgD10 and LgD2 play an important role in regulating the growth, promoting saponin accumulation, and disease resistance of P. polyphylla var. yunnanensis.